The potential utility of synovial C-reactive protein, interleukin-6, and presepsin in diagnostics of periprosthetic joint infection - Lyudmila V. Lyubimova; Svetlana I. Pavlova; Nikolay S. Nikolaev; Evgeniy A. Lyubimov; Nadezhda N. Pchelova; Vladimir Y. Emelianov (Travmatologiâ i Ortopediâ Rossii)
Background. Diagnostics of infectious complications in joint replacement surgery remains a significant challenge, particularly when microbiological analysis of biological material fails to reveal pathogen growth.